Postnationalism and the challenges to European integration in Greece : the transformative power of immigration - Maronitis , Kostas (Palgrave Macmillan, 2020)
Contents: Introduction -- Chapter 1 European Unification and Exclusion Regimes -- Chapter 2 Immigration Policies and the Control of Mobility -- Chapter 3 European Civilisation, National Power and the Detention of Immigrants -- Chapter 4 The New Subjectivity of Nationalism -- Chapter 5 The Social Process of Integration and Religious Tolerance -- Chapter 6 Postnationalism, Solidarity and European Citizenship: Recognising the Transformative Power of Immigration -- Index.